Islamic Financial Institutions’ Perceptions on financing for Public-Private Partnership Projects in Indonesia - Wirdayanti, Yosita Nur; Nidar, Sulaeman Rahman (Jurnal Ekonomi dan Perbankan Syariah, 2024)
Purpose – This paper aims to contribute to the body of knowledge about Islamic Financial Institutions’ (IFIs) intention on financing PPP projects in an Indonesia context, and to offer substantial support to the government to facilitate the implementation of appropriate policies or enact reforms that will encourage increased IFIs financing in PPP projects.Design/methodology/approach – This study developed a theoretical model using the theory of planned behavior (TPB) and subsequently validated it using empirical data gathered from Islamic Financial Institutions in Indonesia. The model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM).Findings – The findings revealed that “subjective norms” and “perceived control behavior” were the significant latent variables impacting IFIs' intention to finance PPP projects. Moreover, the most crucial observable variables affecting the private sector’s intention were “positive attitudes of experienced IFIs,” and “good relationship with PPP implementing company.”Originality – This study highlights a significant deficiency in the existing body of literature. Although there have been several studies on Public-Private Partnerships (PPP) in existing literature, there is a scarcity of study focused on examining the key elements that influence the Islamic Financial Institutions' willingness to finance PPP projects.